Vienskiemenių lietuvių kalbos ištiktukų kelianarių pradinių junginių fonosemantika - Zabarskaitė, Jolanta (Kalbotyra, 2002)
The article deals with the phonotactics and phonosemantics of initial multinomial clusters of monosyllabic interjections in Lithuanian. Distributional data on interjections with two- and tripartite initial combinations of consonants are presented. The article focuses on the phonosemantic connotations of the second consonant in two-partite initial clusters and the phonosemantic connotations of the first consonant in tripartite initial clusters. Pairs of interjections which form phosemantic oppositions are studied, e. g. kliaukšt : kaukš, bliu : bu, skrūpt : krūpt, etc. Their lexical environment is analysed; they are compared to close expressive verbs. The data of the research support the assumption that the sounds in the phonetic structure of the interjection are capable of correlating with particular lexical semes. The phonosemantic connotations of the second consonant in two-partile combinations are close to the phonosemantic connotations of the first consonant in single-partite combinations.